Microglia: a promising therapeutic target in spinal cord injury - Zha, Xiaowei; Zheng, Guoli; Skutella, Thomas; Kiening, Karl; Unterberg, Andreas; Younsi, Alexander (Neural regeneration research, 2025)
Microglia are present throughout the central nervous system and are vital in neural repair, nutrition, phagocytosis, immunological regulation, and maintaining neuronal function. In a healthy spinal cord, microglia are accountable for immune surveillance, however, when a spinal cord injury occurs, the microenvironment drastically changes, leading to glial scars and failed axonal regeneration. In this context, microglia vary their gene and protein expression during activation, and proliferation in reaction to the injury, influencing injury responses both favorably and unfavorably. A dynamic and multifaceted injury response is mediated by microglia, which interact directly with neurons, astrocytes, oligodendrocytes, and neural stem/progenitor cells. Despite a clear understanding of their essential nature and origin, the mechanisms of action and new functions of microglia in spinal cord injury require extensive research. This review summarizes current studies on microglial genesis, physiological function, and pathological state, highlights their crucial roles in spinal cord injury, and proposes microglia as a therapeutic target.
Online veröffentlicht: 16. April 2024
Gesehen am 09.12.2024